Quantitative mass spectrometry reveals dynamics of factor-inhibiting hypoxia-inducible factor-catalyzed hydroxylation. - Singleton, R; Trudgian, D; Fischer, R; Kessler, B; Ratcliffe, P; Cockman, M (2011)
The asparaginyl hydroxylase, factor-inhibiting hypoxia-inducible factor (HIF), is central to the oxygen-sensing pathway that controls the activity of HIF. Factor-inhibiting HIF (FIH) also catalyzes the hydroxylation of a large set of proteins that share a structural motif termed the ankyrin repeat domain (ARD). In vitro studies have defined kinetic properties of FIH with respect to different substrates and have suggested FIH binds more tightly to certain ARD proteins than HIF and that ARD hydroxylation may have a lower K(m) value for oxygen than HIF hydroxylation. However, regulation of asparaginyl hydroxylation on ARD substrates has not been systematically studied in cells. To address these questions, we employed isotopic labeling and mass spectrometry to monitor the accrual, inhibition, and decay of hydroxylation under defined conditions. Under the conditions examined, hydroxylation was not reversed but increased as the protein aged. The extent of hydroxylation on ARD proteins was increased by addition of ascorbate, whereas iron and 2-oxoglutarate supplementation had no significant effect. Despite preferential binding of FIH to ARD substrates in vitro, when expressed as fusion proteins in cells, hydroxylation was found to be more complete on HIF polypeptides compared with sites within the ARD. Furthermore, comparative studies of hydroxylation in graded hypoxia revealed ARD hydroxylation was suppressed in a site-specific manner and was as sensitive as HIF to hypoxic inhibition. These findings suggest that asparaginyl hydroxylation of HIF-1 and ARD proteins is regulated by oxygen over a similar range, potentially tuning the HIF transcriptional response through competition between the two types of substrate.